Prevalence and distribution of non-AIDS causes of death among HIV-infected individuals receiving antiretroviral therapy: a systematic review and meta-analysis - Farahani, Mansour; Mulinder, Holly; Farahani, Alexander; Marlink, Richard (International journal of STD & AIDS, 2017)
The advent of antiretroviral therapy has significantly improved AIDS-related morbidity and mortality. Yet, among people living with HIV, deaths due to non-AIDS-defining illnesses have been on the rise. The objective of this study was to provide information about the global prevalence and distribution of non-AIDS causes of death in the last ten years among people living with HIV receiving antiretroviral therapy, by income levels of countries. We used broad search terms in Google Scholar, PubMed, and EMBASE to identify all studies that investigated the cause of death among people living with HIV receiving antiretroviral therapy, published after January 1, 2005. References were also identified from review articles and reference lists. Inclusion criteria were English language, the study's end date was after 2005, all patients were HIV-positive, at least two-thirds of the patients were receiving antiretroviral therapy, at least one patient died of non-AIDS causes of death. Titles, abstracts, and articles were reviewed by at least two independent readers. Of 2951 titles identified in our original search, 151 articles were selected for further screening. We identified 19 studies meeting our full criteria, with patients from 55 different nations. Pooled non-AIDS causes of death prevalence estimates in high-income countries were 53.0% (95% confidence interval, 43.6-62.3), in developing countries 34.0% (95% confidence interval, 20.3-49.1), and in sub-Saharan countries 18.5% (95% confidence interval, 13.8-23.7). Statistically significant variation was noted within and between categories. Our findings show that a significant number of people living with HIV across the world die from cardiovascular disease, non-AIDS malignancies, and liver disease. There is a global need for further scrutiny in all regions to improve preventive measures and early detection according to distinct causes of death patterns.